2006
DOI: 10.1017/s002531540601366x
|View full text |Cite
|
Sign up to set email alerts
|

Imposex and organotin compounds in marine gastropods and sediments from the Mar del Plata coast, Argentina

Abstract: The occurrence of imposex in Adelomelon brasiliana during two consecutive years near to Mar del Plata (the principal fishery port of Argentina) and its relation to tributyltin (TBT) and dibutyltin (DBT) content in muscle tissue and digestive gland was investigated using gas chromatography. Percentage of imposex affected females increased to over 80% in spring and summer of both years. However, its intensity, given by the relative penis size index (RPSI), fluctuated around low values. Adelomelon brasiliana dige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 16 publications
1
21
0
3
Order By: Relevance
“…[18][19][20] For instance, recent studies have shown that OTCs exposure induces masculinization (imposex) in several mollusca species because of DNA damage-induced errors of replication, also disrupts the antioxidant defense system of some species of mollusca and fish, and eventually causes apoptosis (cell death). [21][22][23] Although the effects of long-term human exposure to OTCs at environmentally realistic levels are unknown, the available information on mammalian toxicity, derived largely from animal and in vitro research, clearly suggest that there are potential risks. Hence, replacement by novel environmentally friendly catalysts for the transesterification is eagerly needed.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] For instance, recent studies have shown that OTCs exposure induces masculinization (imposex) in several mollusca species because of DNA damage-induced errors of replication, also disrupts the antioxidant defense system of some species of mollusca and fish, and eventually causes apoptosis (cell death). [21][22][23] Although the effects of long-term human exposure to OTCs at environmentally realistic levels are unknown, the available information on mammalian toxicity, derived largely from animal and in vitro research, clearly suggest that there are potential risks. Hence, replacement by novel environmentally friendly catalysts for the transesterification is eagerly needed.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] However, OTCs are toxics; it has been shown to be potentially carcinogenic. [15][16][17] Hence, safer catalysts by more environmental friendly are eagerly desired.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were found by Cledón et al (2005) in a population of the snail Adelomelon brasiliana in the same area. On the other hand, the neoformation of multiple penises in females indicates that the sensitivity to TBT is higher in O. deshayesiana than in other snails from the same area, such as Buccinanops monilifer and A. brasiliana, which had lower percentages of impo sex and RPSI values (Cledón et al 2006.…”
Section: Population Structurementioning
confidence: 93%